The Boron Solubility in Al-Mg-B Alloys - J. Zeman; A. Herman; J. Šerák (Archives of Foundry Engineering)
This study deals with the effect of magnesium content in Al-Mg-B alloy (with a boron content of about 5 wt. %) on the formation of intermetallic phases and elimination of inclusions in the form of boron powder particles in the final structure. At first look, the high melting temperature difference between pure aluminium (660°C) and boron (2076°C) appears to be a potential problem. Moreover, boron has a minimal solubility in aluminium (0.055 wt.%) and the liquidus temperature increases very rapidly with increasing boron content (liquidus temperature approx. 1 160°C at 5 wt.% for Al-B binary alloy). Alloying with magnesium results in the transformation of the intermetallic phases AlB12 and AlB2 to the (Al, Mg)B2 phase and has a significant beneficial effect on the formation of intermetallic boron phases in the aluminium alloy without residual boron powder particles.